Psychological Determinants of Academic Achievement in Accounting: Evidence from Brazil - Samuel de Paiva Naves Mamede; Alessandra Vieira Cunha Marques; Pablo Rogers; Gilberto José Miranda (BBR: Brazilian Business Review)
The proposal of this research was to investigate the association between psychological variables and academic performance of 494 students of acco unting o f a Brazilian public U niversity. W e seek , therefore, to highlight some psychological variables to understand the behavior of students of accounting courses. The instrument used for data collection was a questionnaire based on five psychological constructs: self - efficacy, self - esteem, optimism, locus of control and self - control. Regression analyses were used to identify the influence of the explanatory variables on the academic performance coefficient, with the main results showing that: (i) the variable smo king has a direct impact on the academic achievement of students; (ii) the academic performance of women is higher than that of men; (i ii ) students within the age range of 20 to 40 years have significantly lower performance than students of other age range s, and ( i v) the variable experience time in accounting is related with the students' performance.